A Comparative analysis of Intersectionality under Discrimination Law in the Light of Vulnerability Theory as a Post-Identity Approach - Sharma, Shwetank (Christ University Law Journal, 2021)
In spite of the presence of intersectionality as a concept in feminist literature for over twenty-five years, the State Policy, across the world, has been ignorant towards the interplay of identities and its role in the discrimination law jurisprudence. This article claims that a legitimate accommodation of a multi-ground claim under the Right to Equality regime, present in various legal systems, shall be a purposive step towards substantive equality. The article also highlights certain frailties associated with Intersectionality and introduces the age-old dilemma surrounding the formulation of State Policy, as to whether it should be ―identity-neutral‖ like anti-classification principle, or ―identity-sensitive‖ like intersectionality itself. The article also introduces the vulnerability theory proposed by Martha Fineman, as a post identity approach. The final analysis, explains how the two theories can coexist so that the State Policy can move towards substantive equality, and thus, mitigate the horrors of discrimination.